High Seroprevalence of Anti-SARS-CoV-2 Antibodies in Chelsea, Massachusetts. (9th September 2020) - Naranbhai, Vivek; Chang, Christina C; Beltran, Wilfredo F Garcia; Miller, Tyler E; Astudillo, Michael G; Villalba, Julian A; Yang, Diane; Gelfand, Jeffrey; Bernstein, Bradley E; Feldman, Jared; Hauser, Blake M; Caradonna, Timothy M; et al.
Abstract: SARS-CoV-2 antibody testing allows quantitative determination of disease prevalence, which is especially important in high-risk communities. We performed anonymized convenience sampling of 200 currently asymptomatic residents of Chelsea, the epicenter of COVID-19 illness in Massachusetts, by BioMedomics SARS-CoV-2 combined IgM-IgG point-of-care lateral flow immunoassay. The seroprevalence was 31.5% (17.5% IgM + IgG +, 9.0% IgM + IgG −, and 5.0% IgM − IgG + ). Of the 200 participants, 50.5% reported no symptoms in the preceding 4 weeks, of which 24.8% (25/101) were seropositive, and 60% of these were IgM + IgG − . These data are the highest seroprevalence rates observed to date and highlight the significant burden of asymptomatic infection.